Observation of early events in the photoactivation of Myxobacterial phytochrome using time-resolved serial femtosecond crystallography - Tek Narsingh Malla; Luis Aldama; Viridiana Leon; Denisse Feliz; Hao Hu; Isaiah Thomas; Andrea Cellini; Weixiao Y. Wahlgren; Amke Nimmrich; Sabine Botha; Ray Sierra; Mark S. Hunter; et al. (Communications Chemistry)
Abstract Myxobacteria are non-photosynthetic, soil-dwelling bacteria distinguished by a multicellular stage in their life cycle known as fruiting bodies that are stimulated by light. Myxobacterial phytochromes are candidates for the perception of red-light. The mechanism how light is perceived and converted to a physiological response is unknown. Here, time-resolved serial femtosecond crystallographic (TR-SFX) experiments were conducted on microcrystals of the photosensory core module of the Stigmatella aurantiaca bacteriophytochrome 2 (SaBphP2). Initial events of the Z to E isomerization reaction of the covalently bound, open-chain tetrapyrrole biliverdin (BV) chromophore were determined. At 3 ps after light activation, the BV ring-D assumes a configuration needed for the isomerization. At 100 ps, a mixture of BV in the Z or E configuration is observed in subunit A, while in the other subunit the chromophore remains in the Z configuration. In conjunction with prior results, these structures reveal the molecular mechanism of phytochrome activation in the photomorphogenesis of the myxobacteria and provide the molecular foundation for physiological responses to red light in other bacteria.